A study on young consumers’ buying attention towards sex appeal advertising / Nurul Izzati Mohd Usman - Mohd Usman, Nurul Izzati (2016)
In this particular study, the research is purposely narrowing down to a narrow sample group of young consumers’ and it is specifically focus on age between 18 years old until 26 years old. The main study of this research is to identify the dimension that influences the young consumers’ buying intention and to determine the relationship between the dimensions among young consumers’ buying intention. There are five independent variables to be analyzed. The variables are known as (1) Nudity, (2)Sexual behaviours, (3) Physical attractiveness, (4) Sexual referents and (5) Sexual embeds (Lambiase and Reichert, 2003). This research also wanted to study the impact of the sex appeal advertising on young consumer buying intention.